THE STATUS OF READING HABIT AND INTERESTS AMONG SECONDARY SCHOOL CHILDREN IN SRI LANKA - Abeyrathna, P.H.A.S; Zainab, A.N. (Malaysian Journal of Library and Information Science, 2004)
Explores the leisure reading habits and interest among 300 secondary school students from 10 schools in Sri Lanka.The study also observes the students attitude towards reading, their use of the school library and knowledge of how the school library are organised for locating needed materials. The problems students face in obtaining reading materials is also identified. The study uses a structured questionnaire as the survey instrument. The findings generally indicate that the students read regularly outside school hours. This reading however, is mainly confined to textbooks and mainly carried out for the purpose of acquiring knowledge or for study. Consequently, the library is used mainly to study or do homework rather than to borrow items to read at leisure. Most students indicate positive attitude towards the library for providing them with the facility to carry out their study or meet friends, but hardly use the services the library provides. Most express dissatisfaction with their library’s collection.